Correction: Physical crosslinking of hyaluronic acid in the presence of phospholipids in an aqueous nano-environment. Issue 47 (27th November 2018) - Bełdowski, Piotr; Weber, Piotr; Dėdinaitė, Andra; Claesson, Per M.; Gadomski, Adam
Abstract : Correction for 'Physical crosslinking of hyaluronic acid in the presence of phospholipids in an aqueous nano-environment' by Piotr Bełdowski et al., Soft Matter, 2018, DOI: ;10.1039/c8sm01388h .